AB0743 Secukinumab Improves Multiple Parameters of Disease Activity in Subjects with Active Ankylosing Spondylitis Through 52 Weeks of Subcutaneous Therapy: Data From the Phase 3 Measure 2 Study. (9th June 2015) - Braun, J.; Sieper, J.; Aelion, J.; Emery, P.; Deodhar, A.; Porter, B.; Andersson, M.; Richards, H.
Abstract : Background: Disease activity in ankylosing spondylitis (AS) encompasses a wide range of clinical manifestations. As such, a number of composite and single component activity measures exist. Objectives: To describe the effect of subcutaneous (s.c) treatment with secukinumab on multiple parameters of disease activity at Weeks (Wks) 16 and 52 in subjects enrolled in the randomized, double-blind, placebo-controlled, phase 3 MEASURE 2 study (NCT01649375 ). Methods: 219 adults with active AS were randomized to receive s.c. secukinumab 75 mg, 150 mg, or placebo (PBO) at baseline, Wk 1, 2 and 3, and every 4 wks starting at Wk 4. At Wk 16, subjects randomized to PBO were re-randomized to receive secukinumab 150 mg or 75 mg every 4 wks. Disease activity parameters included Ankylosing Spondylitis Disease Activity Score (ASDAS)-C-reactive protein (ASDAS-CRP), ASDAS-erythrocyte sedimentation rate (ASDAS-ESR), and the proportion of subjects achieving ≥50% improvement in Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score (BASDAI50). The effect of secukinumab on individual components of the Assessment of Spondyloarthritis International Society (ASAS) response criteria are also reported: patient's global assessment of disease activity and total spinal pain, both assessed on a visual analogue scale (VAS), Bath Ankylosing Spondylitis Functional Index (BASFI), and spinal inflammation based on BASDAI questions 5 and 6. Results: 84.7% and 82.2% of subjects in the secukinumab 150 and 75 mg arms, respectively, completed 52 wks of treatment. Secukinumab 150 mg s.c. was consistently associated with improvements vs PBO across multiple measures of disease activity at the Wk 16 primary endpoint, including ASDAS-CRP, ASDAS-ESR, patient assessments of disease activity and total spinal pain, BASFI and BASDAI50 (Table ). Improvements in the secukinumab 150 mg s.c. arm were consistently greater than with 75 mg. At Wk 16, a higher proportion of subjects receiving secukinumab 150 mg (47.2%) and 75 mg (38.4%) achieved a clinically important change (decrease of ≥1.1) compared with PBO (18.9%) in ASDAS-CRP. Similarly, more subjects receiving secukinumab 150 mg (48.6%) and 75 mg (42.5%) achieved a clinically important change compared with PBO (20.3%) in ASDAS-ESR at Wk 16. Major improvement (decrease of ≥2.0) in ASDAS-CRP at Wk 16 was achieved in 25.0%, 15.1% and 4.1% of subjects in the secukinumab 150 mg, 75 mg and PBO arms, respectively; equivalent rates for ASDAS-ESR were 27.8%, 17.8% and 8.1% ( P <0.05 for all comparisons vs PBO). Improvements with secukinumab were sustained through 52 wks (Table ). Conclusions: Secukinumab reduced disease activity in subjects with active AS, with approximately 50% of subjects who received the 150 mg dose achieving a clinically important change in ASDAS-CRP and ASDAS-ESR at Wk 16. These improvements were sustained through Wk 52. Acknowledgements: Medical writing support was provided by Rachel Mason at Seren Communications (Tytherington, UK), and was funded by Novartis. Disclosure of Interest: J. Braun Grant/research support from: Abbvie (Abbott), Amgen, BMS, Boehringer-Ingelheim, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB, Consultant for: Abbvie (Abbott), Amgen, BMS, Boehringer-Ingelheim, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB, Speakers bureau: Abbvie (Abbott), Amgen, BMS, Boehringer-Ingelheim, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, and UCB, J. Sieper Grant/research support from: AbbVie, Pfizer, and Merck, Consultant for: AbbVie, Pfizer, Merck, UCB, and Novartis, Speakers bureau: AbbVie, Pfizer, Merck, and UCB, J. Aelion Grant/research support from: AbbVie, Amgen, BMS, Boehringer-Ingelheim, Celgene, Janssen, Eli-Lilly, Norvartis, Pfizer, Takeda, Roche, Sanofi-Aventis, and UCB, Consultant for: AbbVie, Amgen, Celgene, Eli-Lilly, Pfizer, and Takeda, Speakers bureau: AbbVie, Amgen, Celgene, Mallinkroft, and UCB, P. Emery Consultant for: AbbVie, BMS, Merck, Novartis, Pfizer, Roche, and UCB, A. Deodhar Grant/research support from: AbbVie, Celgene, Janssen, Novartis, Pfizer, and UCB, Consultant for: AbbVie, Celgene, Janssen, Novartis, Pfizer, and UCB, B. Porter Shareholder of: Novartis, Employee of: Novartis, M. Andersson Employee of: Novartis, H. Richards Employee of: Novartis